Architecture, experience and image. Exploring Bergson's path - García Moreno, Beatriz (Estudios de Filosofía, 1997)
Contextualism is an interesting way of approaching architectonic work, for its taking into account human act of 'inhabiting'. That view demands from the interpreter to consider not only the incidentality and historical character of the work, but also its relationship to the environment in order to show how special this propasal employing visual and tactile typologics is, the azahar first compares it to those methods focused merely on formal or pre-existing parameters. She brings then into relief the ideas of Henri Bergson, because being he a thinker of contextual thought, he makes il possible, on the one hand, an analyses of image as an element leading to new ideas and changes of meaning, and on the other one, to many a path to interpretation. At last, two works by Osear Niemeyer architect are studied, on whose works the author distinguishes more concretelly the sense of this proposal.